Ki Hajar Dewantara's Noble Values in Traditional Blacksmithing Practices: A Descriptive Study - Rina Agustini; Asep Hidayatullah; Yoni Sunaryo; Etika Rachmawati; Ilah; Ifani Hasbi Aulialillah; Selvia Salwa Firdausi; Siti Rohmah Anjani (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aims to describe the noble values ??of Ki Hajar Dewantara contained in the traditional practices of blacksmiths. The values ??studied include moral values, social values, independence values ??that include independence and responsibility, and cultural values ??or love of the homeland. The method used in this study is a quantitative descriptive method. The data in this study were obtained through a questionnaire technique given to seven blacksmiths as research respondents. The statements in the questionnaire consisted of four aspects, namely moral values, social values, independence values, and cultural values. The data obtained through the questionnaire were analyzed quantitatively using score calculations, averages, and percentages. The results of the study showed that the character values / virtuous values indicator of moral values ??obtained a percentage of 99.4%, honesty and exemplary indicators of 98.2%, social values ??of 97.1%, independence values ??of 94.8%, and cultural values ??of 94.8%. Thus, it can be concluded that the traditional practice of blacksmithing contains the noble values ??of Ki Hajar Dewantara which are reflected through polite attitudes, cooperation, responsibility, independence, and love for local culture as part of character education based on local wisdom.